Ethyl Pyruvate Modulates Murine Dendritic Cell Activation and Survival Through Their Immunometabolism - Chakhtoura, Marita; Chain, Robert W.; Sato, Priscila Y.; Qiu, Connie C.; Lee, Michael H.; Meissler, Joseph J.; Eisenstein, Toby K.; Koch, Walter J.; Caricchio, Roberto; Gallucci, Stefania (Frontiers in Immunology, 2019)
Attenuating the innate immunity activation could ameliorate inflammation and disease in settings such as transplant rejection or autoimmunity. Recently, a pivotal role for metabolic re-programming in TLR-induced dendritic cell (DC) activation has emerged. Ethyl pyruvate (EP), a pyruvate derivative, possesses anti-inflammatory properties in vitro and in animal models of disease. However, its effects on DCs remain elusive. We found that EP attenuated LPS-induced activation of murine GM-CSF bone marrow-derived dendritic cells (DCs) in vitro, reducing pro-inflammatory cytokine and IL-10 production, co-stimulatory molecule and MHC expression, the type I Interferon (IFN-I) response, the LPS-induced cell death, and the ability of DCs to stimulate allogeneic T cells. DC activation induced by TLR7 and TLR9 ligands was also suppressed by EP in vitro. Finally, EP decreased TLR-induced activation stimulated in vivo in conventional DCs and inflammatory monocytes. Investigating EP mechanisms, we found that EP decreased glycolysis and mitochondrial respiration, upon and in absence of TLR stimulation, by reducing ERK-, AKT- and nitric oxide (NO) activation. These results indicate that EP inhibits most of the DC biological responses to TLR triggering, altering the metabolic reprogramming necessary for DC activation.